Personal and Job Characteristics Associated with Underemployment - Wilkins, R (My University, 2006)
Using information collected by the 2001 Household Income and Labour Dynamics in Australia (HILDA) survey, I investigate the factors associated with underemployment, defined as a situation where a part-time employed person would like to work more hours in order to increase income. Multinomial logit models are estimated of labour force status in which underemployment is distinguished from other part-time employment. Effects of a wide range of personal and neighbourhood characteristics are examined, including family background, employment history and local labour market conditions. Underemployment is found to have many predictors in common with unemployment, but also a number of differences. Additional models are estimated on employed persons only that investigate the job characteristics associated with underemployment. Relatively few job characteristics predict underemployment as distinct from other part-time employment.
Melbourne Institute of Applied Economic and Social Research Working Paper Series
Keywords: Employment; Employment -- Underemployment; Labour market; Employment and unemployment